Improving venous symptoms in C0s-C1s patients after multicomponent diosmin-based preparation: Initial experience. (June 2023) - Greco, Michele; Bissacco, Daniele
The use of drug therapies in patients with chronic venous disease (CVD) remains a topic of debate regarding safety, compliance, and effectiveness. Although the beneficial effects of molecules like diosmin have been established in patients with chronic venous insufficiency (CVI) of C3–C6 classes, the evidence for its use in C0–C1 patients is not well documented. This report aims to describe and analyze the positive impact of a new diosmin-based drug therapy on a population of C0–C1 patients in terms of relief of venous symptoms.